A CORRELATIONAL STUDY ON QUALITY OF LIFE AND COPING STRATEGY AMONG DIALYSIS PATIENTS IN SELECTED HOSPITAL AT MANGALORE - Raju, Rekha; S., Latha (Journal of Health and Allied Sciences NU, 2012)
A descriptive study was conducted on the Quality of life and coping strategy of dialysis patients from 01.08.2011 to 01.10.2011. The purpose of this study was to describe the Quality of life and Coping strategy among dialysis patients in selected hospital. Rating scales were used to measure the Quality of life & Coping strategy of 60 dialysis patients selected by Purposive sampling technique. The findings of the study showed that majority of the dialysis patients 68.3% (41) had average quality of life. Highest percentage 81.7%(49) had satisfactory coping. 31.7%(19) of dialysis patients were in the age group of 61-70 yrs, majority of the dialysis patients were males 68.3%(41), 85% of the subjects were married, 46.7%(28) of them had completed secondary & higher secondary education, 55%(33) of them were unemployed, 60%(36) of them had an income less than 5000 Rupees/month, 83.3%(50) of the subjects were Hindus,57%(37) were undergoing dialysis for a duration of 0-12 months. The correlation coefficient value of Quality of life and Coping strategy was 0.431 (p<.05) & hence there is positive correlation between Quality of life and Coping strategy. Study findings also revealed that there is significant association between the Quality of life and religion.
Keywords: Quality of life; Coping strategy; Dialysis patients